Analysis of the relight of post-mastectomy breast reconstruction (Research, Society and Development, 2022)
Background: The mastectomy is a required and often healing procedure in the treatment of breast cancer, however it meddles the quality of life and body image of the women, since the breast is a symbol of femininity. Regarding this issue, academy research points that breast reconstruction surgery, after the mastectomy, the femininity symbol is restored and hence the improvement of self steem and reduction of depression state and sexual disfunction. Objective: Analyze the importance of the breast reconstruction surgery after a mastectomy procedure performed for a invasive treatment of breast cancer. Methods: This is a narrative literature review using the PUBMED database and the books Moore e Oncoplastia and Reconstrução Mamária. Results and conclusion: this review concludes that recent data shows a correlation between improvement of quality of life and breast resconstruction surgery after a mastectomy procedure, including reduction of depression state and enhancement of self acceptance and sexual drive. Even though the improvement beeing considered significant, it must be taken into account that the woman has had a great impact on her life, including a physical change in the texture of the reconstructed breast compared to her natural breast, thus, each one takes time to deal with the new situation, requiring family and psychological support, even after reconstruction.